2014
DOI: 10.7314/apjcp.2014.15.17.7187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pre-Operation Diagnosis of Thyroid Cancer with Fine Needle Aspiration and Core-needle Biopsy: a Meta-analysis

Abstract: Background:The aim of this meta-analysis was to compare sensitivities and specificities of fine needle aspiration (FNA) and core needle biopsy (CNB) in the diagnosis of thyroid cancer. Materials and Methods: Articles were screened in Medline, the Cochrane Library, EMBASE and Google Scholar, and subsequently included and excluded based on the patient/problem-intervention-comparison-outcome (PICO) principle. Primary outcome was defined in terms of diagnostic values (sensitivity and specificity) of FNA and CNB fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 39 publications
(58 reference statements)
1
24
1
1
Order By: Relevance
“…A recent meta-analysis by Li et al [20] found that FNA and CNB do not differ significantly in sensitivity and specificity for diagnosis of thyroid malignancy, concordant with our results. The areas under the ROC curves of FNA were even higher than those of CNB without statistical significance (0.905 ± 0.030 for FNA vs. 0.745 ± 0.095, for CNB, P = 0.053) [20].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A recent meta-analysis by Li et al [20] found that FNA and CNB do not differ significantly in sensitivity and specificity for diagnosis of thyroid malignancy, concordant with our results. The areas under the ROC curves of FNA were even higher than those of CNB without statistical significance (0.905 ± 0.030 for FNA vs. 0.745 ± 0.095, for CNB, P = 0.053) [20].…”
Section: Discussionsupporting
confidence: 92%
“…The areas under the ROC curves of FNA were even higher than those of CNB without statistical significance (0.905 ± 0.030 for FNA vs. 0.745 ± 0.095, for CNB, P = 0.053) [20]. This meta-analysis included the aforementioned study by Sung et al along with four other studies [6,9,18,19,21].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations